Enhancing student engagement in information systems education – a longitudinal case study from a Sino-Foreign university - Bayley, Trevor C.R. (2017)
This doctoral thesis describes five years of research on an undergraduate accounting information systems module at the China campus of Nottingham University Business School. The central research question is ‘How can small group interactions be designed to improve student engagement in information systems education?’. To this end, an interpretive philosophical paradigm is adopted to address three research questions which are explored in distinct phases: In the first phase a grounded approach is taken to address the question - What influences engagement in small group interactions? The second phase takes the themes identified in the first phase and addresses the question - What strategies might be adopted to address these influences? In the third and final phase, a longitudinal study is conducted, in which the strategies identified in the second phase are then applied, in 3 cycles of action research, addressing the question – How, why and what would be good practice in implementing such strategies? This research finds 36 themes that influence engagement in small group interactions, strategies are then identified to address those themes and those within the scope of control of the researcher are tested. This research confirms that the findings in the extant literature relating to mainland Chinese undergraduate student engagement, in Western undergraduate programmes overseas, also apply to such programmes conducted in the mainland Chinese context. In addition a sense of student empowerment over influencing pedagogy to suit preference in terms of classroom environment, interaction timing, second language use, and tutor focus is found. Among the strategies tested, a problem-based group project, set within a familiar context and informed by an evidence-based design approach, which values the opinion and experience of the student as designer of the proposed problem solution, was found to be the most effective in promoting early engagement in the desired learning process. This study supports the argument that case study approaches, where those studies are set in unfamiliar contexts, may not be best suited for undergraduate programmes due to their inherent contextual uncertainties. This research finds that, through adopting an evidence-based approach to research for such group projects, student evaluation of their own experience and insights changes positively, enabling more rounded and reflective critical argument and decision-making. This work may be seen to contribute to fill gaps both in evidence from practice and in the body of ‘scientific’ evidence in respect of the following contexts, such gaps having been identified by the cited authors as follows: Theoretical contributions 1. Research into the area of Chinese student engagement in Western educational settings e.g. Li and Campbell (2008). 2. Qualitative research methods in general and the adaptation of western approaches to the Chinese context e.g. Watkins-Mathys (2007). 3. Literature relating to evidence-based design in teaching and learning e.g. Groccia and Buskist (2011), Rousseau and Mc Carthy (2007), Wastell (2011) and Ahmadi et al. (2012). 4. Literature relating to alignment of the expectation gap between tutors and students in cross-cultural settings e.g. Zhou et al. (2008). 5. Literature relating to evidence-based design in information systems and accounting literature e.g. Marr (2009), Baskerville (2011), Wastell (2011). Practical contributions 6. The call for case studies that “lionise” evidence-based design and avoid the contextual challenges of [case study] approaches e.g. Starkey and Tempest (2009) and Wastell (2011). 7. Further evidence from the process of adapting British teaching and learning practices for use in the Chinese undergraduate context (Zhou et al., 2008). 8. Further evidence to inform both student/staff induction processes and the body of research on the design of teaching and learning practices at NUBS in China e.g. Waters (2007).